A New Allele of the SPIKE1 Locus Reveals Distinct Regulation of Trichome and Pavement Cell Development and Plant Growth - Liang, Shuang; Yang, Xuying; Deng, Meng; Zhao, Jun; Shao, Jingxia; Qi, Yafei; Liu, Xiayan; Yu, Fei; An, Lijun (Frontiers in Plant Science, 2019)
The single-celled trichomes of Arabidopsis thaliana have long served as an elegant model for elucidating the mechanisms of cell differentiation and morphogenesis due to their unique growth patterns. To identify new components in the genetic network that governs trichome development, we carried out exhaustive screens for additional Arabidopsis mutants with altered trichome morphology. Here we report one mutant, aberrantly branched trichome1-1 (abt1-1), with a reduced trichome branching phenotype. After positional cloning, a point mutation in the SPIKE1 (SPK1) gene was identified in abt1-1. Further genetic complementation experiments confirmed that abt1-1 is a new allele of SPK1, so abt1-1 was renamed as spk1-7 according to the literatures. spk1-7 and two other spk1 mutant alleles, covering a spectrum of phenotypic severity, highlighted the distinct responses of developmental programs to different SPK1 mutations. Although null spk1 mutants are lethal and show defects in plant stature, trichome and epidermal pavement cell development, only trichome branching is affected in spk1-7. Surprisingly, we found that SPK1 is involved in the positioning of nuclei in the trichome cells. Lastly, through double mutant analysis, we found the coordinated regulation of trichome branching between SPK1 and two other trichome branching regulators, ANGUSTIFOLIA (AN) and ZWICHEL (ZWI). SPK1 might serve for the precise positioning of trichome nuclei, while AN and ZWI contribute to the formation of branch points through governing the cMTs dynamics. In summary, this study presented a fully viable new mutant allele of SPK1 and shed new light on the regulation of trichome branching and other developmental processes by SPK1.